Synthetic Approaches to Mono- and Bicyclic Perortho-Esters with a Central 1,2,4-Trioxane Ring as the Privileged Lead Structure in Antimalarial and Antitumor-Active Peroxides and Clarification of the Peroxide Relevance - Griesbeck, Axel G. (Molecules, 2017)
The synthesis of 4-styryl-substituted 2,3,8-trioxabicyclo[3.3.1]nonanes, peroxides with the core structure of the bioactive 1,2,4-trioxane ring, was conducted by a multistep route starting from the aryl methyl ketones 1a–1c. Condensation and reduction/oxidation delivered enals 4a–4c that were coupled with ethyl acetate and reduced to the 1,3-diol substrates 6a–6c. Highly diastereoselective photooxygenation delivered the hydroperoxides 7a–7c and subsequent PPTS (pyridinium-p-toluenesulfonic acid)-catalyzed peroxyacetalization with alkyl triorthoacetates gave the cyclic peroxides 8a–8e. These compounds in general show only moderate antimalarial activities. In order to extend the repertoire of cyclic peroxide structure, we aimed for the synthesis of spiro-perorthocarbonates from orthoester condensation of β-hydroxy hydroperoxide 9 but could only realize the monocyclic perorthocarbonate 10. That the central peroxide moiety is the key structural motif in anticancer active GST (glutathione S-transferase)-inhibitors was elucidated by the synthesis of a 1,3-dioxane 15—with a similar substitution pattern as the pharmacologically active peroxide 11—via a singlet oxygen ene route from the homoallylic alcohol 12.